Allogeneic transplantation provides durable remission in a subset of DLBCL patients relapsing after autologous transplantation. (15th March 2016) - Fenske, Timothy S.; Ahn, Kwang W.; Graff, Tara M.; DiGilio, Alyssa; Bashir, Qaiser; Kamble, Rammurti T.; Ayala, Ernesto; Bacher, Ulrike; Brammer, Jonathan E.; Cairo, Mitchell; Chen, Andy; Chen, Yi‐Bin; et al.
Summary: For diffuse large B‐cell lymphoma (DLBCL) patients progressing after autologous haematopoietic cell transplantation (autoHCT), allogeneic HCT (alloHCT) is often considered, although limited information is available to guide patient selection. Using the Center for International Blood and Marrow Transplant Research (CIBMTR) database, we identified 503 patients who underwent alloHCT after disease progression/relapse following a prior autoHCT. The 3‐year probabilities of non‐relapse mortality, progression/relapse, progression‐free survival (PFS) and overall survival (OS) were 30, 38, 31 and 37% respectively. Factors associated with inferior PFS on multivariate analysis included Karnofsky performance status (KPS) <80, chemoresistance, autoHCT to alloHCT interval <1‐year and myeloablative conditioning. Factors associated with worse OS on multivariate analysis included KPS<80, chemoresistance and myeloablative conditioning. Three adverse prognostic factors were used to construct a prognostic model for PFS, including KPS<80 (4 points), autoHCT to alloHCT interval <1‐year (2 points) and chemoresistant disease at alloHCT (5 points). This CIBMTR prognostic model classified patients into four groups: low‐risk (0 points), intermediate‐risk (2‐5 points), high‐risk (6‐9 points) or very high‐risk (11 points), predicting 3‐year PFS of 40, 32, 11 and 6%, respectively, with 3‐year OS probabilities of 43, 39, 19 and 11% respectively. In conclusion, the CIBMTR prognostic model identifies a subgroup of DLBCL patients experiencing long‐term survival with alloHCT after a failed prior autoHCT.